(untitled) (Scientific journal of the Fergana State University, 2023)
The obligation to improve our nation’s defense falls squarely on each of us. The state’s defense system depends on youth education, political awareness, employment, and scientific and technological advancement. The goal of education is to prepare people to undertake a variety of social roles by orienting them toward mental and physical work as well as other beneficial activities for society. An essential component of it is military patriotic education, and for this reason it’s crucial to help young people reach adulthood by developing their mental maturity and physical health. The human aspect is addressed using the technique and scientific underpinnings of military patriotism education. This idea encompasses a person’s overall ideological-political, spiritual, physical, and other characteristics. In this article, ideas and opinions are expressed regarding the training regimen used to develop physical stamina for military service.